Explaining Pension Fund Product and Governance Disclosure in Australia - Monica Guo-Sze Tan; Marie-Anne Cam (Australasian Accounting, Business and Finance Journal, 2013)
Fund disclosure is an important communication tool between trustees and fund members for product comparison and credibility verification. We examine what drives Australian not-forprofit superannuation funds to disclose their fund product information to the market. Our research derives a model that shows how the proprietary costs of disclosure and fund governance drive the disclosure of information about trustee, investment agents, fees, and overall practices. The research findings indicate that disclosure costs have a significant negative influence on voluntary disclosure, while board size has a weak positive relation with disclosure. Board independence is an unreliable and insignificant explanatory variable for voluntary disclosure. We discuss how the multi-layer agency relationship and institutional factors in the superannuation funds industry influence the power of these factors and their effects on voluntary disclosure.
Keywords: Fund disclosure; not for profit superannuation fund; superannuation; disclosure